A right to privacy as a fundamental human right in correlation with data protection - Ninkov, Ivona (Bánki Közlemények, 2019)
This paper presents a general overview of the rights to privacy as a fundamental human right in the correlation with data protection. The paper aims to illustrate how rights of privacy are developed after the Second World War and the data protection regulation after the case of Snowdan. It clarifies the difference between the right to privacy and data protection in the lights of the General Data Protection Regulation, which entered into force on May 25th, 2018. The paper outlines data protection terminology, people’s rights and how these rights are enforced through international legal treaties. During the research the author used a comparative method to find the similarity and differencies between the privacy rights and personal data protection focusing on the rich jurisprudence of the European Court of Human Rights (ECtHR) and the Court of Justice of the European Union (CJEU). In the paper it is concluded that the right of privacy and the right of personal data protection are closely linked, but they should not be considered to be identical.